Influence of Severity of Anemia on Clinical Findings in Infants with Sickle Cell Anemia: Analyses from the BABY HUG Study - Lebensburger, Jeffrey D. (2011)
BACKGROUND: Clinical complications of sickle cell anemia begin in infancy. BABY HUG (ClinicalTrials.gov, NCT00006400) was a NHLBI-NICHD supported randomized phase III placebo-controlled trial of hydroxyurea (HU) in infants (recruited at 9–18 months) unselected for clinical severity with sickle cell anemia. This secondary analysis of data from BABY HUG examines the influence of anemia on the incidence of sickle cell related complications, and the impact of hydroxyurea therapy in altering these events by comparing children with lower (<25(th) percentile) and higher (>75(th) percentile) hemoglobin concentrations at study entry. PROCEDURE: Infants were categorized by: 1) age-adjusted hemoglobin quartiles as determined by higher (Hi) and lower (Lo) hemoglobin concentrations at study entry (9 to12 months old: <8.0 gm/dL and >10.0gm/dL; 12 to 18 months old: <8.1 gm/dL and >9.9gm/dL) and 2) treatment arm (hydroxyurea or placebo). Four subgroups were created: placebo (PL) LoHb (n=25), PL HiHb (n=27), hydroxyurea (HU) LoHb (n=21), and HU HiHb (n=18). The primary and secondary endpoints of BABY HUG were analyzed by subgroup. RESULTS: Infants with lower hemoglobin at baseline were more likely to have a higher incidence of clinical events (acute chest syndrome, pain crisis, fever) as well as higher TCD velocities and lower neuropsychological scores at study exit. Hydroxyurea reduced the incidence of these findings. CONCLUSION: Infants with more severe anemia are at risk for increased clinical events that may be prevented by early initiation of hydroxyurea.